Status of Medical Physiologist and Medical Physiology Teaching: Bangladesh Perspective - Latif, Shah Abdul; Hossain, Mahfuza (Journal of Bangladesh Society of Physiologist, 2010)
The status of physiologist and physiology in medical colleges and institutes has been a concern of the physiological societies and Bangladesh Society of Physiological (BSP) as well. The newly formed BPS has undertaken an initiative the future of the medical physiologist and learning objective of the medical physiology education in Bangladesh. DOI: 10.3329/jbsp.v4i2.4168 J Bangladesh Soc Physiol. 2009 Dec;4(2): 24